2022
DOI: 10.1155/2022/4179116
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Path Deduction from Folk Art to Stage Art in the Change of Geographical Environment: Take Anhui Flower Drum Lantern as an Example

Abstract: Anhui flower drum lantern, as a folk dance in the Huaihe River Basin, exudes the local cultural atmosphere and expresses the cultural color of song and dance drama incisively and vividly. At the same time, it is a sacrificial activity with social belief. As a typical example of the development of folk activities in Anhui, it is an important intangible cultural heritage. With the accelerating construction of economic globalization and social innovation, the pursuit of “cultural confidence” has gradually become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%